Emission trading applications in the European Union and the case of Turkey as an emerging market - (:unkn) unknown (My University, 2011)
Purpose: The purpose of this paper is to analyze emission trading applications in the European Union (EU) and to benefit from its experiences; also to discuss different types of energy financing mechanisms for Turkey, an emerging market which faces a fast growth of energy demand. Design/methodology/approach: The Kyoto Protocol and its market-based flexible mechanisms to reduce emissions worldwide are explained. The logic and development phases of an emission trading scheme (ETS) started in 2005 in the EU are given in response to this protocol's targets. With lessons learned from the ETS, the position of Turkey in terms of greenhouse gas emissions and its strategy to find solutions for a low carbon economy are underlined, as it can be assumed to be a reference point for other emerging markets. Findings: This ETS became the main vehicle for EU member states to enforce themselves, to be in line with their Kyoto's emission reduction targets via some mechanisms and it has the potential to be leader in the formation of a global emission trading program. It made possible the transfer of technology and experience to emerging countries. Turkey should be aware and well prepared, for the post-Kyoto period, to benefit from similar mechanisms to finance its energy investments. Practical implications: The paper is a useful source of information for ETS. Social implications: This paper gives information on emission reduction mechanisms used worldwide by countries which aim to be a low carbon economy. Originality/value: This paper fulfils a resource need for the structure of ETS and the position of Turkey as an emerging market with Kyoto's Protocol. © Emerald Group Publishing Limited.
Keywords: Emerging markets; Emission trading; Emission trading scheme; European Union; Kyoto Protocol; Renewable energy; Turkey